Respuesta :
Step-by-step explanation:
The first thing we have to do before we can actually do the problem is turn the words into a math equation.
If we use x as our "number," we see that "The sum of a number and 2" can also be written as x+2. The word "Is" almost always means (=), so now we have (x+2) = . The very last part, "6 less than twice that number," means 2x - 6.
So, our whole equation is, (x + 2) = (2x - 6), which simplifies to -x = -8, or
x = 8
Answer:
y = 8
Step-by-step explanation:
number = y
y + 2 = 2y - 6
y + 2 - 2 = 2y - 6 - 2
y = 2y - 8
y - 2y = 2y - 2y - 8
- y = - 8
- y × - 1 = - 8 × - 1
y = 8